The New Testament in its ritual world - DeMaris, Richard E. (Oxford ; New York : Routledge, 2008)
This work offers new and insightful perspectives on early Christian communities and their cultural environment, through exploration of rituals central to Greco-Roman life.
Introduction : ritual studies and the New Testament -- Entry rites. Perilous passage -- Contested waters -- And the greatest of these is death -- Exit rites. Paul's omphalos -- Jesus jettisoned.
Includes bibliographical references and index.
Keywords: Church history -- Primitive and early church, ca. 30-600.; Ritual; Rites and ceremonies; Ritualism; RELIGION -- Biblical Studies -- New Testament; Electronic books